PENGGUNAAN MEDIA SOSIAL SEBAGAI MEDIA KOMUNIKASI PUBLIK PEMERINTAH PROVINSI SUMATERA SELATAN - Putri Papani, Yuliana; Komaruddin, Komaruddin; Setiawan, M.Arif (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This research focuses on the use of social media by public relations of the South Sumatra Provincial Government. Public Relations of the South Sumatra Provincial Government is a government agency responsible for communication to the public. The development of communication and information technology requires public relations practitioners, including government public relations, to be able to adapt and choose new media channels that are effective in conducting public communication. So this study aims to find out how to use social media as a public communication medium of the South Sumatra Provincial Government. This study uses a qualitative method with a descriptive approach where the researcher tries to explain and describe information about the use of social media managed by the Public Relations of the South Sumatra Provincial Government to the public. Data collection techniques are carried out by interviews and observations. The results of the study show that the public relations of the South Sumatra Provincial Government has used social media in public communication activities as a platform to promote and disseminate government programs and policies so that they can be known to the public. Based on the theory of Excellece Public Relations, communication activities that have been established have been running in two directions, but still use a two-way asymmetric model where agencies expect the public to continue to act, think and behave according to the government's will through active publications that tend to be "telling" about various leadership activities without listening to the wishes of the community.